2016
DOI: 10.1590/1413-70542016406010416
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic behavior of a combined anaerobic-aerobic system employed in the treatment of vinasse

Abstract: The understanding of reactor hydrodynamics is essential for improving the performance of a reactor and biogas production. This study sought to evaluate the hydrodynamic behavior of a combined anaerobic-aerobic system at a laboratory scale for treating vinasse. The experiment was conducted in a system using two UASB reactors connected in series, followed by an Aerated Submerged Biological Filter (ASBF). The flow rates applied to the system and the corresponded theoretical HRTs in the UASB1, UASB2 and ASBF were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Greater oscillations in the tracer response occurred at an HRT of 14 h, which may be resulted from the internal recirculation of this tracer in the reactor. Fia et al (2016) also observed a delay in the response of the tracer, which may be linked to adsorption of the tracer by the biomass, or the existence of internal recirculation zones or dead zones inside the UASB reactors and ASBF, characterized by isolated or inaccessible regions where the imprisoned fluid does not interact with active regions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Greater oscillations in the tracer response occurred at an HRT of 14 h, which may be resulted from the internal recirculation of this tracer in the reactor. Fia et al (2016) also observed a delay in the response of the tracer, which may be linked to adsorption of the tracer by the biomass, or the existence of internal recirculation zones or dead zones inside the UASB reactors and ASBF, characterized by isolated or inaccessible regions where the imprisoned fluid does not interact with active regions.…”
Section: Resultsmentioning
confidence: 98%
“…It causes inversion of the gradient and diffusion begins to occur in the opposite direction. Fia et al (2016) and Zeng et al (2013) attributed this phenomenon to the tracer diffusion between the biofilm and substrate, considerable diffusion of the tracer into the biofilm, presence of dead zones or stagnation of the reactor, or eventually hydraulic short circuiting. Pérez-Pérez et al (2017) concluded that the presence of zeolite, used as material support in an expanded granular sludge bed (EGSB) reactor, caused higher values of dead zones, ranging from 12.3% to 24.2% and stated that the higher the zeolite bed the higher the percentage of dead zones in the EGSB reactor.…”
Section: Resultsmentioning
confidence: 99%
“…Em relação à hidrodinâmica do reator, sabe-se que esta pode ser influenciada pelas características de mistura, presença de zonas mortas, curtos-circuitos e caminhos preferenciais, que normalmente não são consideradas na maioria dos modelos aplicados para digestão anaeróbia. Simulação em dinâmica de fluidos computacional (CFD) (Passos et al, 2014;Cruz et al, 2016) e testes experimentais de laboratório (técnicas de estímulo-resposta com traçadores e modelos relacionados) (Fia et al, 2016) são métodos adequados para avaliar a hidrodinâmica do reator. Além disso, a CFD tem uma vantagem adicional, pois pode ser usada em grande medida para substituir experimentos demorados e caros (Pourtousi et al, 2015).…”
Section: Introductionunclassified
“…A determinação da DTR é relativamente simples e Levenspiel (1999) apresenta uma das referências teóricas mais conhecidas sobre este assunto. Estudos anteriores sobre a hidrodinâmica UASB mostraram que eles poderiam ser bem descritos pelo modelo do número de tanques em série (NTIS) (Fia et al, 2016).…”
Section: Introductionunclassified
“…O aumento da taxa de aeração pode melhorar as condições hidrodinâmicas dos reatores e acelerar a transferência de massa de OD. Tais condições influenciam diretamente a transferência de massa gás-líquido em um processo e dependem de condições operacionais tais como propriedades físico-químicas da cultura, geometria do reator e presença de organismos consumidores de oxigênio (GARCIA-OCHOA, 2009;TANG, 2017;FIA et al, 2016). Ao se projetar um reator, é fundamental levar em ( )…”
Section: Aeraçãounclassified